Patients' perceptions of visual impairment associated with smoking: A cross-sectional study of a United Kingdom tertiary eye centre. Issue 1 (January 2022) - Baker, Diya; Akpenyi, Onyinye; Shahzad, Haris; Mellington, Faye
Smoking is a well-established risk factor for several eye disorders including cataracts and age-related macular degeneration. While many individuals are informed of the various adverse health effects, there is limited research into patients' awareness of the relationship between smoking and eye disease and the potential impact this might have on reducing smoking behaviour. Our findings document the low level of awareness of the risk of blindness from smoking at a tertiary eye unit in the United Kingdom and highlight the need for increased involvement from eye care professionals, alongside health campaigns to educate the public of this consequence of smoking.